The Implementation of Microsite-Assisted Gamification to Improve Students’ Memory Retention in Mathematics Learning - Maula, Minhatul; Haqq, Arif Abdul; Lestiana, Herani Tri (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2025)
This study was motivated by the urgency of utilizing technological advancements in education to optimize students' memory retention in mathematics learning, which is known to require deep and continuous conceptual understanding. The objective of this research is to investigate the improvement of students' memory retention after the implementation of gamification supported by a microsite in mathematics learning. The research employed a quantitative approach with a population consisting of all 10th-grade students at SMA Negeri 1 Sumber in the 2024/2025 academic year, totaling 439 students. The sample was selected using cluster random sampling, specifically class X-7 consisting of 35 students. Data collection techniques included a memory retention test and unstructured interviews. The data were analyzed using the N-Gain formula and a paired sample t-test. The results of the study showed an improvement in students' memory retention in the class that implemented gamification supported by a microsite, with the improvement categorized as high. Based on the hypothesis testing, students' memory retention after the implementation of gamification supported by a microsite was significantly better compared to before the implementation. Therefore, gamification supported by a microsite has been proven effective in enhancing students' memory retention in mathematics learning.